EFL Students’ Perception in Learning Reading Comprehension through Literature Circle - Kamalia, Nabila; Puspitaloka, Nina; Pahlevi, Muhammad Reza (Peneliti.net, 2024)
The aimed of this research is to find out students’ perception regarding literature circle in learning reading comprehension. This research used a descriptive case study method with a qualitative approach. Observation and interview are used as data collection. Data analysis proposed by Miles & Huberman was used in this research. 8th grade of junior high school students at one of the schools in Karawang were participants in this research. The findings of this research indicate that students’ perception provide a positive response in learning reading comprehension using LC. Students feel motivated to learn during discussions, it can help them improve their ability to understand text and vocabulary, besides that their learning process becomes more enjoyable. In conclusion, LC can be a learning method that can help students improve their reading comprehension skills.